Behavior Monitoring in the Middle Grades: Evaluation of the Classroom Performance Survey. Issue 6 (3rd July 2022) - Caldarella, Paul; Larsen, Ross A. A.; Williams, Leslie; Lulla, Saanya R.; Wills, Howard P.
ABSTRACT: Middle level school teachers commonly measure and monitor students' academic performance, but such is not the case for students' classroom behavior. This is unfortunate, given the rise in students' classroom behavior problems in middle school, especially for students who experience emotional or behavioral disorders. The Classroom Performance Survey (CPS) is a brief behavior rating scale that has shown promise for use in elementary school settings, but no studies have investigated the psychometric properties of this measure in middle level schools. In the present study, 103 middle grades students at-risk for emotional or behavioral disorders were rated by their classroom teachers using the CPS. We conducted a psychometric evaluation using a multi-step analytic strategy, including confirmatory factor analysis and reliability analysis. Results showed that the CPS displayed evidence of a reliable two-factor structure (Academic Competence and Interpersonal Competence), predictive validity with academic outcomes (percent of assignments completed and student grades), convergent validity with established behavioral and observational measures, and sensitivity to change over time. Study results suggest positive implications for using the CPS as part of behavior intervention and monitoring efforts in middle level schools.